Cultural Translation Evaluation: Development of a Scale for English Majors' Oral Narrative Competence in Telling Chinese Stories—Validation Based on the Rasch Model (Journal of Education, Humanities, and Social Research, 2025)
This study assesses English majors' proficiency in narrating Chinese stories in English, focusing on their ability to bridge linguistic and cultural gaps. Grounded in cultural translation theory, it highlights the importance of both linguistic accuracy and cultural nuance. The study developed a 15-item assessment scale using the Rasch model, ensuring precision and fairness. The scale covers four dimensions: cultural accuracy, language expression, narrative structure, and cross-cultural interaction. Through literature review and interviews with educators and students, the scale was refined to address challenges like cultural misinterpretations and narrative flow. Results show the scale's high reliability and validity, emphasizing the need to cultivate intercultural communication skills. This research offers a practical tool for enhancing English majors' narrative abilities, helping them improve both linguistic expression and cultural understanding, thus fostering effective cross-cultural communication in academic and real-world contexts.